PENGGUNAAN CaCO3 UNTUK MEMPERTAHANKAN KUALITAS TEKSTUR DAN SIFAT ORGANOLEPTIK PISANG AMBON (Musa acuminata) SELAMA PENYIMPANAN - Santi Weliana; Eva Ramalia Sari; Jusuf Wahyudi (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2014)
During the handling of bananas, maturation process cause of deterioration or damage. When the maturation get faster, the banana gets damaged before it reaches the consumer. The purpose of this study is to determines the influence of immersion and the use of CaCO3 on banana quality  during storage. The research method used in this study are soaking ambon bananas using CaCO3 levels by 1%, 5% and 2% with time soaking for 90 minutes, 120 minutes and 150 minutes than stored at room temperature for 4 days. The analysis of this research are texture and sensory analysis. The analysis showed that the best treatment is immersion in 2 % CaCO3 during 150 minutes with 11.66 mm a penetration rate, and hard old green sensory scale.Keywords: CaCO3, Immersion, Ambon BananaDuring the handling of bananas, maturation process cause of deterioration or damage.When the maturation get faster, the banana gets damaged before it reaches the consumer.The purpose of this study is to determines the influence of immersion and the use of CaCO3on banana quality during storage. The research method used in this study are soakingambon bananas using CaCO3 levels by 1%, 5% and 2% with time soaking for 90 minutes,120 minutes and 150 minutes than stored at room temperature for 4 days. The analysis ofthis research are texture and sensory analysis. The analysis showed that the best treatmentis immersion in 2 % CaCO3 during 150 minutes with 11.66 mm a penetration rate, andhard old green sensory scale.Keywords: CaCO3, Immersion, Ambon Banana